THE COMPARATIVE ANALYSIS OF PURCHASE DECISION ON E-SHOP MATAHARIMALL.COM AND LAZADA.CO.ID - Pio, Tirsa Petra; Kindangen, Paulus .; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2017)
Abstract: This research will analyze purchase decision on two e-comers, which are mataharimall.com and lazada.co.id. Both of them claim they are number one online shopping in Indonesia. This research conducts objective to know the differences in purchase decision based on security factor, brand factor, price factor, promotion factor and information factor between Mataharimall.com and Lazada.co.id users in Manado. But both are still have the advantages and disadvantages of Mataharimall.com and Lazada.co.id. The averages indicators ofÂ purchase decisionÂ are brand,Â price, promotion, security and information. And its depends to consumer to choose where they want to shopping. There is no significant difference in purchase decision based on security factors between both online shop, there is no significant difference in purchase decision based on brand factors between both online shop, there is asignificant difference in purchase decision based on price factors between both online shop, there is no significant difference in purchase decision based on promotion factors between both online shop, there is no significant difference in purchase decision based on information factors between both online shop. Keyword: online shop, purchase decision